Preoperative risk assessment with computed tomography in patients undergoing lung cancer surgery - Ueda, Kazuhiro; Murakami, Junichi; Tanaka, Toshiki; Hayashi, Masataro; Okabe, Kazunori; Hamano, Kimikazu (Journal of Thoracic Disease, 2018)
Background: Although whole lung computed tomography (CT) is included in the routine workup before lung cancer surgery, it is not utilized to assess the preoperative pulmonary function. Methods: Two hundred ninety patients (development cohort) who underwent lung lobectomy for cancer in our institute and another 100 patients (validation cohort) who subsequently underwent the same operation in a referral hospital were included. The total lung volume (TLV) and emphysematous lung volume (ELV) were obtained by quantitative CT. Results: The TLV was higher in patients with a smoking history than in those without. The ELV to the TLV was higher in elderly patients than in younger patients. The regression equation for forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1) were developed using CT-derived variables, together with sex, age, height, and smoking habit, by a multiple regression analysis in the development cohort. The regression equation-based FVC and 1 were significantly correlated with the actual FVC and 1 in the development cohort, as well as in the validation cohort. The predicted postoperative 1 (ppo%1) calculated based on the regression equation was also correlated with the postoperative 1 value obtained by the conventional method (R=0.53), and the regression equation-based ppo%1 was a significant predictor of postoperative cardiopulmonary complications (P=0.02). Conclusions: Whole lung CT can be used to assess the preoperative pulmonary function in patients undergoing lobectomy for cancer. This method may be helpful in preoperative risk assessment, particularly in patients who have difficulty in implementation of spirometry.